A comparative study on deformation mechanisms, microstructures and mechanical properties of wide thin-ribbed sections formed by sideways and forward extrusion. (September 2021) - Zhou, Wenbin; Yu, Junquan; Lu, Xiaochen; Lin, Jianguo; Dean, Trevor A.
Abstract: Extruded profiles/sections are increasingly used in the transport industry for lightweight structures. In this paper, a wide thin-ribbed aluminium profile with asymmetric Z-shape, was manufactured by a novel sideways extrusion process proposed by the authors. A comparative study was conducted by utilising the direct/forward extrusion process at the same extrusion temperature and speed, in which the different process mechanics, resulting microstructures and mechanical properties of profiles have been investigated by experiments and finite element modelling. It was revealed that, compared with sideways extrusion, although the design of a die pocket in forward extrusion induces preform and avoids the use of the large-diameter billet and extrusion container/press needed for extruding wide profiles, it requires a greater extrusion force due to work-piece upsetting necessary to fill the die pocket and leads to a lower effective strain in the profile rib. EBSD characterisation of the regions with an equal effective strain indicated that an increased shear strain is more efficient for obtaining fine grains with a higher average misorientation angle. In the same region of the profile rib made from the two different processes, sideways extrusion results in greater grain refinement due to greater effective strains, and a slightly greater texture intensity was found due to the intensive shear deformation. Tensile tests on formed profiles revealed that sideways extrusion leads to a higher yield strength (YS) and ultimate tensile strength (UTS) but a relatively lower elongation to failure, due to the combined effects of grain refinement, GND and texture intensity enhancement. Compared with the billet, the profile formed by forward and sideways extrusion has a YS increased by about 60% and 79% respectively, and an UTS increased by about 74% and 80% respectively in the extrusion direction, demonstrating an advantage of the sideways extrusion process in improving material strength under the same extrusion condition. Graphical abstract: Image 1 Highlights: Wide thin-ribbed aluminium profiles were manufactured by sideways and forward extrusion at the same condition. Deformation mechanisms, resulting microstructures and mechanical properties for the two processes were compared. Sideways extrusion requires a lower extrusion force but results in higher effective strains in the profile rib. Sideways extrusion leads to greater grain refinement, yield strength and ultimate tensile strength. Strength and ductility are improved simultaneously for the profile formed by sideways extrusion at elevated temperature.